Retroelement decay by the exonuclease XRN1 is a viral mimicry dependency in cancer - Hosseini, A; Lindholm, HT; Chen, R; Mehdipour, P; Marhon, SA; Ishak, CA; Moore, PC; Classon, M; Di Gioacchino, A; Greenbaum, B; De Carvalho, DD (Cell Press, 2024)
Viral mimicry describes the immune response induced by endogenous stimuli such as double-stranded RNA (dsRNA) from endogenous retroelements. Activation of viral mimicry has the potential to kill cancer cells or augment anti-tumor immune responses. Here, we systematically identify mechanisms of viral mimicry adaptation associated with cancer cell dependencies. Among the top hits is the RNA decay protein XRN1 as an essential gene for the survival of a subset of cancer cell lines. XRN1 dependency is mediated by mitochondrial antiviral signaling protein and protein kinase R activation and is associated with higher levels of cytosolic dsRNA, higher levels of a subset of Alus capable of forming dsRNA, and higher interferon-stimulated gene expression, indicating that cells die due to induction of viral mimicry. Furthermore, dsRNA-inducing drugs such as 5-aza-2'-deoxycytidine and palbociclib can generate a synthetic dependency on XRN1 in cells initially resistant to XRN1 knockout. These results indicate that XRN1 is a promising target for future cancer therapeutics.